MEMBANGUN MODEL PEMBELAJARAN BERBASIS KONTEKSTUAL (CTL) DALAM PENDIDIKAN KARAKTER SISWA SD DI KOTA MEDAN. - Sorta Simanjuntak (LPPM Universitas Negeri Medan, 2012)
The research objective is to build: 1) the model of studing the basic ofCTL the character education for primary students; 2) to know about the competenceof teacher to build and implementation of CTL in learning; 3) to know about theconstribution of CTL in learning the character build for primary students; 4) toknow about the process learning with CTL learning in education of primarystudents in Medan. This study uses the